Polishing composition, polishing method and method for manufacturing semiconductor substrate
By using polyoxane chain water-soluble polymer in the polishing composition, the problems of polishing speed and surface defects of silicon-molybdenum alloys are solved, achieving a more efficient polishing process and a lower defect rate.
Patent Information
- Application Number
- JP2023169594
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
When the prior art uses chemical mechanical polishing (CMP) method, it is difficult to effectively suppress the polishing speed of silicon-molybdenum alloy, and there are many defects such as organic residues on the surface after polishing.
A polishing composition containing a polyoxane chain water-soluble polymer has a molecular weight of between 200 and 600 and a mass fraction of the components containing 700 or above is between 0% and 1%, as a polishing speed inhibitor and a surface defect reducing agent.
It effectively suppresses the polishing speed of silicon-molybdenum alloy, and significantly reduces defects such as organic residues on the surface after polishing, improving the polishing quality.
Smart Images

Figure 2025059488000001 
Figure 2025059488000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]
[0002] In recent years, new microfabrication technologies have been developed to accompany the high integration and high performance of LSI (Large Scale Integration). Chemical Mechanical Polishing (CMP) is one of these technologies, and is frequently used in the LSI manufacturing process, particularly in the multi-layer wiring formation process, for planarizing interlayer insulating films, forming metal plugs, and forming embedded wiring (damascene wiring).
[0003] CMP has been applied to various processes in semiconductor manufacturing, such as the gate formation process in transistor fabrication, where silicon-containing materials such as silicon, silicon oxide (SiO2), polysilicon (polycrystalline silicon), and silicon nitride (Si3N4) are polished.
[0004] As a technique for polishing such silicon-containing materials, for example, Patent Document 1 describes a polishing composition containing abrasive grains having silanol groups and a nonionic water-soluble polymer having a polyoxyalkylene chain, and when the polishing composition is left to stand for one day in an environment at a temperature of 25° C., the abrasive grains have a surface area of 1 μm 2 A polishing composition is disclosed which is characterized in that 5,000 or more molecules of the water-soluble polymer are adsorbed per particle. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-21292 A Summary of the Invention [Problem to be solved by the invention]
[0006] The technology described in Patent Document 1 has the effect of suppressing the polishing rate of polysilicon, but has a problem in that the reduction of defects (e.g., organic residues) on the polished object (polished object) after polishing is insufficient, and there is room for improvement in this regard.
[0007] Therefore, an object of the present invention is to provide a means capable of suppressing the polishing rate of polysilicon and further reducing defects (such as organic residues) on the surface of polished polysilicon. [Means for solving the problem]
[0008] The present inventors have conducted intensive research in view of the above problems. As a result, they have found that the above problems can be solved by a polishing composition containing abrasive grains, a polishing rate suppressor that suppresses the polishing rate of polysilicon, and a defect reducing agent that reduces defects on the surface of polysilicon, wherein the polishing rate suppressor is a water-soluble polymer having a polyoxyalkylene chain and has a number average molecular weight of 200 or more and 600 or less, and the content of a component having a molecular weight of 700 or more is more than 0 mass% and less than 1 mass%, and thus completed the present invention. Effect of the Invention
[0009] According to the present invention, it is possible to provide a means capable of suppressing the polishing rate of polysilicon and further reducing defects (eg, organic residues) on the surface of the polished polysilicon. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] According to one embodiment of the present invention, there is provided a polishing composition containing abrasive grains, a polishing rate suppressor for suppressing the polishing rate of polysilicon, and a defect reducing agent for reducing defects on the surface of polysilicon, wherein the polishing rate suppressor is a water-soluble polymer having a polyoxyalkylene chain and a number average molecular weight of 200 or more and 600 or less, and a content of a component having a molecular weight of 700 or more is more than 0 mass% and less than 1 mass%. According to such a polishing composition of the present invention, the polishing rate of polysilicon can be suppressed, and defects (e.g., organic residues) on the surface of the polysilicon after polishing can be further reduced.
[0011] It is known that water-soluble polymers having polyoxyalkylene chains have the effect of suppressing the polishing rate of polysilicon. However, the technology described in Patent Document 1 has a phenomenon in which the reduction of defects (e.g., organic residues) on the polished object (polished object) after polishing is insufficient, and there is room for improvement in this respect.
[0012] In view of such a phenomenon, the present inventors have conducted extensive research. As a result, the present inventors have surprisingly found that the above-mentioned problems can be solved by using a water-soluble polymer having a polyoxyalkylene chain with a number average molecular weight of 200 or more and 600 or less, and containing a small amount of a component with a molecular weight of 700 or more (the content is more than 0 mass% and less than 1 mass%) as a polishing rate suppressor for suppressing the polishing rate of polysilicon. That is, the present inventors have found that a polishing composition can be obtained that is capable of suppressing the polishing rate of polysilicon and is excellent in reducing defects (e.g., organic residues) on the surface of the polished polysilicon, and have completed the present invention.
[0013] The embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the claims. The embodiments described in this specification can be combined in any way to form other embodiments. In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.
[0014] In this specification, residue refers to foreign matter that adheres to the surface of the polished object.The example of residue is not particularly limited, but can be, for example, organic residue, particle residue derived from abrasive grain contained in polishing composition, residue made of components other than particle residue and organic residue, mixture of particle residue and organic residue, and other residues.
[0015] In this specification, the organic residue refers to a component of the foreign matter adhering to the surface of the polished object, which is composed of organic matter such as organic low molecular weight compounds and polymeric compounds, organic salts, etc. Examples of the organic residue adhering to the polished object include pad waste generated from the pad used in the polishing step described below, or components derived from additives contained in the polishing composition used in the polishing step.
[0016] In addition, since the organic residue is significantly different from other residues in color and shape, whether the residue is an organic residue can be determined by visual inspection, for example, by observation with a scanning electron microscope (SEM). In addition, whether the residue is an organic residue can be determined by elemental analysis using an energy dispersive X-ray analyzer (EDX) attached to the SEM, as necessary. The number of organic residues can be measured using a wafer defect inspection device, or a wafer defect inspection device and SEM or EDX elemental analysis. Specifically, it can be measured by the method described in the examples.
[0017] In this specification, "water-soluble" means that the solubility in water (25°C) is 1 g / 100 mL or more, and "polymer" means a (co)polymer having at least one of a weight average molecular weight (Mw) and a number average molecular weight (Mn) of 200 or more.
[0018] [Abrasive grain] The polishing composition according to the present invention contains abrasive grains. The abrasive grains have the function of mechanically polishing an object to be polished, and increase the polishing rate of the object to be polished by the polishing composition.
[0019] The abrasive grains used in the polishing composition of the present invention include, for example, metal oxides such as silica, alumina, zirconia, titania, etc. The abrasive grains may be used alone or in combination of two or more kinds. The abrasive grains may be either commercially available or synthetic.
[0020] The type of abrasive grain is preferably silica, more preferably colloidal silica. The colloidal silica can be produced by a sodium silicate method or a sol-gel method, and colloidal silica produced by any of these methods can be suitably used as the colloidal silica according to the present invention. However, from the viewpoint of reducing metal impurities, colloidal silica produced by the sol-gel method is preferred. Colloidal silica produced by the sol-gel method is preferred because it contains less metal impurities and corrosive ions such as chloride ions that have the property of diffusing in semiconductors. The production of colloidal silica by the sol-gel method can be carried out using a conventionally known method, and specifically, colloidal silica can be obtained by carrying out a hydrolysis-condensation reaction using a hydrolyzable silicon compound (e.g., alkoxysilane or its derivative) as a raw material. In addition, a commercially available colloidal silica may be used.
[0021] The shape of colloidal silica is not particularly limited, and may be spherical or non-spherical.Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulging out more than the ends, donuts in which the center of a disk is penetrated, plates, so-called cocoons with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, so-called confetti-shaped shapes with multiple protrusions on the surface, and rugby ball shapes, and are not particularly limited.
[0022] In the polishing composition of the present invention, the colloidal silica may have a cationic group on the surface. That is, the colloidal silica may be a cation-modified colloidal silica (cation-modified colloidal silica). As the cation-modified colloidal silica, colloidal silica with an amino group fixed on the surface is preferably mentioned. As a method for producing colloidal silica with such a cationic group, as described in JP-A-2005-162533, a method of fixing a silane coupling agent with an amino group such as aminoethyltrimethoxysilane, aminopropyltrimethoxysilane, aminoethyltriethoxysilane, aminopropyltriethoxysilane, aminopropyldimethylethoxysilane, aminopropylmethyldiethoxysilane, aminobutyltriethoxysilane, etc. on the surface of silica particles can be mentioned. As a result, colloidal silica with an amino group fixed on the surface (amino group-modified colloidal silica) can be obtained.
[0023] In addition, in the polishing composition of the present invention, the colloidal silica may have an anionic group on the surface. That is, the colloidal silica may be anion-modified colloidal silica (anion-modified colloidal silica). As the anion-modified colloidal silica, preferred examples include colloidal silica with an anionic group such as carboxylic acid group, sulfonic acid group, phosphonic acid group, aluminic acid group, etc. fixed on the surface. The method for producing such colloidal silica with an anionic group is not particularly limited, and examples thereof include a method of reacting a silane coupling agent having an anionic group at the end with colloidal silica.
[0024] As a specific example, sulfonic acid groups can be fixed to colloidal silica by the method described in, for example, "Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups", Chem. Commun. 246-247 (2003). Specifically, a silane coupling agent having a thiol group such as 3-mercaptopropyltrimethoxysilane is reacted with colloidal silica, and then the thiol group is oxidized with hydrogen peroxide to obtain colloidal silica having sulfonic acid groups fixed on the surface (sulfonic acid fixed colloidal silica, sulfonic acid modified colloidal silica).
[0025] Carboxylic acid groups can be immobilized on colloidal silica by, for example, the method described in "Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel", Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photoreactive 2-nitrobenzyl ester is coupled to colloidal silica, followed by light irradiation to obtain colloidal silica with carboxylic acid groups immobilized on the surface (carboxylic acid immobilized colloidal silica, carboxylic acid modified colloidal silica).
[0026] Among these, from the viewpoint of further suppressing the polishing rate of polysilicon and further reducing defects on the surface of the polished polysilicon, the abrasive grains are preferably anion-modified colloidal silica, and more preferably colloidal silica having sulfonic acid groups fixed to the surface (sulfonic acid-fixed colloidal silica, sulfonic acid-modified colloidal silica).
[0027] The size of the abrasive grains according to the present invention is not particularly limited. For example, the average primary particle diameter of the abrasive grains is preferably 5 nm or more, more preferably 10 nm or more, even more preferably 15 nm or more, and particularly preferably 20 nm or more. As the average primary particle diameter of colloidal silica increases, the polishing speed of the object to be polished by the polishing composition increases. In addition, the average primary particle diameter of the abrasive grains is preferably 200 nm or less, more preferably 150 nm or less, even more preferably 100 nm or less, and particularly preferably 50 nm or less. As the average primary particle diameter of the abrasive grains decreases, it becomes easier to obtain a surface with fewer defects by polishing using the polishing composition. That is, the average primary particle diameter of the abrasive grains is preferably 5 nm or more and 200 nm or less, more preferably 10 nm or more and 150 nm or less, even more preferably 15 nm or more and 100 nm or less, and particularly preferably 20 nm or more and 50 nm or less. The average primary particle diameter of the abrasive grains can be calculated, for example, based on the specific surface area (SA) of the abrasive grains calculated by the BET method, assuming that the shape of the abrasive grains is a true sphere.
[0028] The average secondary particle diameter of the abrasive grains is not particularly limited, but is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and particularly preferably 25 nm or more. As the average secondary particle diameter of the abrasive grains increases, the resistance during polishing decreases, enabling stable polishing. In addition, the average secondary particle diameter of the abrasive grains is preferably 400 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, and particularly preferably 100 nm or less. As the average secondary particle diameter of the abrasive grains decreases, the surface area per unit mass of the abrasive grains increases, the frequency of contact with the object to be polished increases, and the polishing rate increases. That is, the average secondary particle diameter of the abrasive grains is preferably 10 nm or more and 400 nm or less, more preferably 15 nm or more and 300 nm or less, even more preferably 20 nm or more and 200 nm or less, and particularly preferably 25 nm or more and 100 nm or less. The average secondary particle diameter of the abrasive grains can be measured, for example, by a dynamic light scattering method represented by a laser diffraction scattering method.
[0029] The average degree of association of the abrasive grains is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less. As the average degree of association of the abrasive grains decreases, defects can be reduced more. The average degree of association of the abrasive grains is also preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. As the average degree of association of the abrasive grains increases, there is an advantageous effect that the polishing speed of the object to be polished by the polishing composition is improved. That is, the average degree of association of the abrasive grains is preferably 1.0 or more and 5.0 or less, more preferably 1.5 or more and 4.0 or less, and even more preferably 2.0 or more and 3.0 or less. This average degree of association is obtained by dividing the value of the average secondary particle diameter of the abrasive grains by the value of the average primary particle diameter.
[0030] The upper limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably less than 2.0, more preferably 1.8 or less, and even more preferably 1.5 or less. In this range, defects on the surface of the object to be polished can be further reduced. The aspect ratio is the average of the values obtained by taking the smallest rectangle that circumscribes the image of the abrasive grains by a scanning electron microscope, and dividing the length of the long side of the rectangle by the length of the short side of the same rectangle, and can be determined using general image analysis software. The lower limit of the aspect ratio of the abrasive grains in the polishing composition is not particularly limited, but is preferably 1.0 or more.
[0031] The size of the abrasive grains (average primary particle size, average secondary particle size, average degree of association, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.
[0032] The concentration (content) of the abrasive grains in the polishing composition is not particularly limited. In the case of the polishing composition that is used as it is as a polishing liquid for polishing the object to be polished (typically a slurry-like polishing liquid, sometimes referred to as working slurry or polishing slurry), the lower limit of the concentration (content) of the abrasive grains in the polishing composition is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, more preferably 0.6 mass% or more, even more preferably 0.8 mass% or more, and particularly preferably 1 mass% or more, based on the total mass of the polishing composition. In addition, the upper limit of the concentration (content) of the abrasive grains in the polishing composition is preferably 15 mass% or less, more preferably 10 mass% or less, more preferably 8 mass% or less, even more preferably 6 mass% or less, and particularly preferably 5 mass% or less, based on the total mass of the polishing composition.
[0033] That is, in the case of a polishing composition that is used as is as a polishing liquid for polishing an object to be polished, the concentration (content) of the abrasive grains is preferably 0.1 mass% or more and 15 mass% or less, more preferably 0.5 mass% or more and 10 mass% or less, even more preferably 0.6 mass% or more and 8 mass% or less, even more preferably 0.8 mass% or more and 6 mass% or less, and particularly preferably 1 mass% or more and 5 mass% or less, relative to the total mass of the polishing composition.
[0034] In addition, in the case of a polishing composition that is diluted and used for polishing (i.e., a concentrated solution, an undiluted solution of a working slurry), the concentration (content) of the abrasive grains is usually appropriate to be 30% by mass or less, and more preferably 25% by mass or less, from the viewpoints of storage stability, filterability, etc. In addition, from the viewpoint of utilizing the advantages of making the solution into a concentrated solution, the concentration (content) of the abrasive grains is preferably more than 1% by mass, and more preferably 2% by mass or more.
[0035] When the polishing composition contains two or more types of abrasive grains, the concentration (content) of the abrasive grains means the total amount of these.
[0036] [Polishing speed suppressor] The polishing composition according to the present invention contains a polishing rate suppressor that suppresses the polishing rate of polysilicon. The polishing rate suppressor can be adsorbed on the surface of polysilicon to form a protective film, and has the effect of inhibiting the mechanical polishing action of abrasive grains.
[0037] The polishing rate suppressor is a water-soluble polymer having a polyoxyalkylene chain, the number average molecular weight of which is 200 or more and 600 or less, and the content of components having a molecular weight of 700 or more is more than 0 mass% and less than 1 mass%. Examples of the water-soluble polymer having a polyoxyalkylene chain include polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene glycol, polytetramethylene ether glycol, polypentylene glycol, polyhexylene glycol, polyheptylene glycol, polyoctylene glycol, polynonylene glycol, polydecylene glycol, polyoxyethylene nonylphenyl ether (POE nonylphenyl ether); at least two kinds of block copolymers or random copolymers selected from polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; random copolymers or block copolymers of ethylene oxide and propylene oxide, and ethylene oxide and butylene oxide; polyglycerin, polyethylene oxide-polyvinyl alcohol graft copolymer; and the like. Among these, the polishing rate suppressor is preferably at least one selected from the group consisting of polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and polyglycerin, more preferably at least one selected from the group consisting of polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, and particularly preferably polypropylene glycol.
[0038] The number average molecular weight (Mn) of the water-soluble polymer having a polyoxyalkylene chain is 200 or more and 600 or less. When the number average molecular weight is less than 200, the ability to suppress the polishing rate of polysilicon is weak, and it is not possible to adjust the polishing rate of polysilicon to any desired value. When the number average molecular weight exceeds 600, the water-soluble polymer having a polyoxyalkylene chain is easily adsorbed onto polysilicon, attracting organic residues by hydrophobic interaction and increasing the number of defects. The number average molecular weight is preferably 250 or more, more preferably 300 or more, and more preferably 350 or more. The number average molecular weight of the water-soluble polymer having a polyoxyalkylene chain is preferably 580 or less, more preferably 560 or less, and even more preferably 540 or less. That is, the number average molecular weight of the water-soluble polymer having a polyoxyalkylene chain is preferably 250 or more and 580 or less, more preferably 300 or more and 560 or less, and even more preferably 350 or more and 540 or less. The number average molecular weight of the water-soluble polymer having a polyoxyalkylene chain can be measured by gel permeation chromatography (GPC), and the details of the measurement method will be described in the Examples.
[0039] In addition, the water-soluble polymer having a polyoxyalkylene chain has a content of components having a molecular weight of 700 or more that is more than 0% by mass and less than 1% by mass. When the content of components having a molecular weight of 700 or more is 0% by mass, the suppression of the polishing rate of polysilicon is insufficient. On the other hand, when the content of components having a molecular weight of 700 or more is 1% by mass or more, defects on the surface of the polished polysilicon increase. The content of components having a molecular weight of 700 or more is preferably 0.1% by mass or more, more preferably 0.15% by mass or more, and even more preferably 0.2% by mass or more. The content of components having a molecular weight of 700 or more is preferably 0.95% by mass or less, more preferably 0.85% by mass or less, and even more preferably 0.5% by mass or less. That is, the content of components having a molecular weight of 700 or more is preferably 0.1% by mass or more and 0.95% by mass or less, more preferably 0.15% by mass or more and 0.85% by mass or less, and even more preferably 0.2% by mass or more and 0.5% by mass or less.
[0040] The content of components having a molecular weight of 700 or more in the water-soluble polymer having a polyoxyalkylene chain can be controlled, for example, by subjecting the water-soluble polymer having a polyoxyalkylene chain to an activated carbon treatment. Specifically, for example, the activated carbon treatment method is carried out by preparing an aqueous solution of a water-soluble polymer having a polyoxyalkylene chain at an arbitrary concentration, and then mixing and stirring the aqueous solution with activated carbon, thereby adsorbing and removing components having a molecular weight of 700 or more on the activated carbon. After the activated carbon treatment, the used activated carbon can be removed from the aqueous solution of the water-soluble polymer having a polyoxyalkylene chain by using a filter. More specifically, the method described in the examples can be adopted.
[0041] Furthermore, by appropriately selecting the mixing mass ratio and mixing two or more water-soluble polymers having polyoxyalkylene chains with different contents of components having a molecular weight of 700 or more, it is possible to obtain the target water-soluble polymer having a polyoxyalkylene chain with a content of components having a molecular weight of 700 or more exceeding 0% by mass and less than 1% by mass. The temperature and time during mixing are not particularly limited.
[0042] The content of components having a molecular weight of 700 or more in the water-soluble polymer having a polyoxyalkylene chain can be measured by the following method. That is, any water-soluble polymer having a polyoxyalkylene chain is separated into each polymer using high performance liquid chromatography (HPLC). Then, the sum of the peak areas of the polymers having a molecular weight of 700 or more is divided by the total area of all peaks obtained from the water-soluble polymer having a polyoxyalkylene chain to obtain the content (abundance ratio). More specifically, it can be measured by the measurement method described in the Examples.
[0043] The polishing rate suppressor may be used alone or in combination of two or more. In addition, the polishing rate suppressor may be a commercially available product or a synthetic product.
[0044] The lower limit of the concentration (content) of the polishing rate suppressor in the polishing composition is not particularly limited, but is preferably 0.05 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.15 mass% or more, and particularly preferably 0.2 mass% or more. The upper limit of the concentration (content) of the polishing rate suppressor in the polishing composition is preferably 5 mass% or less, more preferably 3 mass% or less, even more preferably 1 mass% or less, and particularly preferably less than 1 mass%. That is, the concentration (content) of the polishing rate suppressor in the polishing composition is preferably 0.05 mass% or more and 5 mass% or less, more preferably 0.1 mass% or more and 3 mass% or less, even more preferably 0.15 mass% or more and 1 mass% or less, and particularly preferably 0.2 mass% or more and less than 1 mass%. In addition, when the polishing composition contains two or more polishing rate suppressors, the concentration (content) of the polishing rate suppressor means the total amount of these.
[0045] [Defect reduction agent] The polishing composition according to the present invention contains a defect-reducing agent that reduces defects on the surface of polysilicon. The defect-reducing agent is adsorbed on the surface of polysilicon and has the effect of changing the wettability of the polysilicon surface from hydrophobic to hydrophilic. The action of the defect-reducing agent can prevent re-adhesion of residues, etc. to the surface of the polished object.
[0046] The defect reducing agent used in the present invention is not particularly limited as long as it has the above-mentioned effect, and examples thereof include those containing an alcoholic hydroxyl group, a carboxyl group, an acyloxy group, a sulfo group, a quaternary ammonium structure, a heterocyclic structure, and a vinyl structure in the molecule. From the viewpoint of more easily obtaining the effect of the present application, the defect reducing agent is preferably a water-soluble polymer having an alcoholic hydroxyl group in the side chain.
[0047] The water-soluble polymer having an alcoholic hydroxyl group in the side chain is not particularly limited, but is preferably a compound having a vinyl alcohol unit (a structural portion represented by -CH2-CH(OH)-; hereinafter also referred to as "VA unit") in its structure.
[0048] The compound containing a VA unit in its structure may have all repeating units substantially composed of VA units. The compound containing a VA unit in its structure may further contain a non-vinyl alcohol unit (a structural unit derived from a monomer other than vinyl alcohol, hereinafter also referred to as a "non-VA unit") in addition to the VA unit. The non-VA unit is not particularly limited, and examples thereof include structural units derived from ethylene, vinyl acetate, vinyl propionate, vinyl hexanoate, 2-butenediol, etc. When a polymer containing a structural unit derived from vinyl alcohol contains a non-VA unit, it may contain only one type of non-VA unit, or may contain two or more types of non-VA units. In the compound containing a VA unit in its structure, the ratio of the number of moles of the VA unit to the number of moles of all repeating units is not particularly limited, but is preferably 50% or more, more preferably 65% or more, even more preferably 70% or more, and particularly preferably 75% or more (upper limit 100%).
[0049] The water-soluble polymer having an alcoholic hydroxyl group in its side chain is preferably at least one selected from the group consisting of polyvinyl alcohol, polyvinyl alcohol derivatives (polyvinyl alcohol derivatives having an alcoholic hydroxyl group in its side chain), copolymers of vinyl alcohol and other monomers (copolymers of vinyl alcohol and other monomers having an alcoholic hydroxyl group in its side chain), and derivatives of said copolymers (derivatives of copolymers of vinyl alcohol having an alcoholic hydroxyl group in its side chain and other monomers).
[0050] The degree of saponification of polyvinyl alcohol is not particularly limited, but is preferably 50 mol % or more, more preferably 65 mol % or more, even more preferably 70 mol % or more, and particularly preferably 75 mol % or more (upper limit 100 mol %).
[0051] An example of a polyvinyl alcohol derivative is modified polyvinyl alcohol, etc. Modified polyvinyl alcohol contains a structure in which a part of the alcoholic hydroxyl group of the vinyl alcohol unit is substituted with another functional group as a non-VA unit (hereinafter, also referred to as a "modified VA unit").
[0052] The modified polyvinyl alcohol is not particularly limited, but examples thereof include carboxy-modified polyvinyl alcohol, sulfonic acid-modified polyvinyl alcohol, phosphoric acid-modified polyvinyl alcohol, silanol-modified polyvinyl alcohol, epoxy-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, nitrile-modified polyvinyl alcohol, pyrrolidone-modified polyvinyl alcohol, silicone-modified polyvinyl alcohol, amino-modified polyvinyl alcohol, quaternary amino-modified polyvinyl alcohol, etc. In addition, the modified polyvinyl alcohol is not particularly limited, but examples thereof include compounds obtained by cyclic acetalization of polyvinyl alcohol (e.g., polyvinyl butyral, polyvinyl propylal, polyvinyl ethylal, polyvinyl methylal, etc.).
[0053] The derivatives of copolymers of vinyl alcohol and other monomers are not particularly limited, and examples thereof include compounds that further contain, in addition to VA units and modified VA units, structural units such as structural units derived from ethylene, structural units derived from vinyl ethers having a long-chain alkyl group, and structural units derived from compounds having at least one of an acryloyl group and a methacryloyl group.
[0054] Polysaccharides are also preferably used as the water-soluble polymer having an alcoholic hydroxyl group in the side chain. Examples of polysaccharides include dextrin, maltodextrin, isomaltodextrin (branched maltodextrin), cyclodextrin, branched cyclodextrin, roasted dextrin, polymeric dextrin, indigestible dextrin, inulin, inulin hydrolyzate, agave inulin, LM pectin, HM pectin, pullulan, guar gum, guar gum hydrolyzate, xanthan gum, gum arabic, gum ghatti, native gellan gum, deacylated gellan gum, locust bean gum, tara gum, galactomannan, glucomannan, konjac mannan, curdlan, karage, etc. Examples of suitable sugars include cellulose gum, maltose, maltose, maltitol, maltitol esters ...
[0055] Among these, the defect reducing agent is more preferably at least one selected from the group consisting of polyvinyl alcohol, sulfonic acid modified polyvinyl alcohol, and vinyl alcohol-butenediol copolymer, and further preferably a vinyl alcohol-butenediol copolymer.
[0056] The weight average molecular weight of the defect reducing agent is not particularly limited, but is preferably 1,000 or more, preferably 3,000 or more, and more preferably 5,000 or more. The weight average molecular weight of the defect reducing agent is not particularly limited, but is preferably 1,000,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less. That is, the weight average molecular weight of the defect reducing agent is preferably 1,000 or more and 1,000,000 or less, preferably 3,000 or more and 100,000 or less, and even more preferably 5,000 or more and 50,000 or less.
[0057] The defect-reducing agent may be used alone or in combination of two or more. In addition, the defect-reducing agent may be a commercially available product or a synthetic product.
[0058] The lower limit of the concentration (content) of the defect reducing agent in the polishing composition is preferably 0.005 mass% (50 mass ppm) or more, more preferably 0.01 mass% (100 mass ppm) or more, even more preferably 0.015 mass% (150 mass ppm) or more, and particularly preferably 0.02 mass% (200 mass ppm) or more, from the viewpoint of further increasing the hydrophilicity of the polishing object. The upper limit of the concentration (content) of the defect reducing agent in the polishing composition is preferably 1 mass% (10000 mass ppm) or less, more preferably 0.8 mass% (8000 mass ppm) or less, even more preferably 0.5 mass% (5000 mass ppm) or less, even more preferably 0.3 mass% (3000 mass ppm) or less, and particularly preferably 0.1 mass% (1000 mass ppm) or less. That is, the concentration (content) of the defect reducing agent in the polishing composition is preferably 0.005 mass% (50 mass ppm) or more and 1 mass% (10000 mass ppm) or less, more preferably 0.01 mass% (100 mass ppm) or more and 0.8 mass% (8000 mass ppm) or less, even more preferably 0.015 mass% (150 mass ppm) or more and 0.5 mass% (5000 mass ppm) or less, even more preferably 0.02 mass% (200 mass ppm) or more and 0.3 mass% (3000 mass ppm) or less, and particularly preferably 0.02 mass% (200 mass ppm) or more and 0.1 mass% (1000 mass ppm) or less. Note that, when the polishing composition contains two or more kinds of defect reducing agents, the concentration (content) of the defect reducing agent means the total amount of these.
[0059] [Inorganic salts] The polishing composition according to the present invention preferably contains an inorganic salt. The inorganic salt increases the electrical conductivity of the polishing composition and compresses the electric double layer on the surface of the object to be polished (e.g., silicon oxide) containing a material other than polysilicon. Therefore, the action of the abrasive grains is improved, and the polishing speed of materials other than polysilicon can be improved.
[0060] Examples of inorganic salts include sodium nitrate, potassium nitrate, ammonium nitrate, magnesium nitrate, calcium nitrate, sodium nitrite, potassium nitrite, lithium carbonate, sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, ammonium carbonate, sodium bicarbonate, sodium sulfate, potassium sulfate, ammonium sulfate, calcium sulfate, magnesium sulfate, sodium sulfite, potassium sulfite, calcium sulfite, magnesium sulfite, potassium thiosulfate, lithium sulfate, magnesium sulfate, sodium thiosulfate, sodium hydrogen sulfite, sodium hydrogen sulfate, potassium hydrogen sulfate, lithium fluoride, sodium fluoride, potassium fluoride, calcium fluoride, ammonium fluoride, potassium chloride, sodium chloride, ammonium chloride, calcium chloride, potassium bromide, sodium bromide, ammonium bromide, calcium bromide, sodium iodide, potassium iodide, potassium triiodide, calcium iodide, trilithium phosphate, tripotassium phosphate, trisodium phosphate, triammonium phosphate, sodium monohydrogen phosphate, potassium monohydrogen phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, and ammonium dihydrogen phosphate. These inorganic salts may be used alone or in combination of two or more. In addition, the inorganic salts to be used may be commercially available products or synthetic products.
[0061] Among these inorganic salts, ammonium sulfate, ammonium nitrate, ammonium carbonate, triammonium phosphate, and diammonium phosphate are preferred because they are free of metals and halogens. The use of inorganic salts free of metals and halogens leads to advantages such as suppression of metal residues, improved safety in handling, and prevention of corrosion of the object to be polished.
[0062] The concentration (content) of the inorganic salt in the polishing composition is not particularly limited. In the case of the polishing composition used as it is as a polishing liquid for polishing the object to be polished, the lower limit of the concentration (content) of the inorganic salt in the polishing composition is preferably 0.2 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.4 mass% or more, and particularly preferably 0.5 mass% or more, based on the total mass of the polishing composition. In addition, the upper limit of the concentration (content) of the inorganic salt in the polishing composition is preferably 3.0 mass% or less, more preferably 2.5 mass% or less, even more preferably 2.0 mass% or less, and particularly preferably 1.5 mass% or less, based on the total mass of the polishing composition.
[0063] That is, the concentration (content) of the inorganic salt is preferably 0.2 mass% or more and 3.0 mass% or less, more preferably 0.3 mass% or more and 2.5 mass% or less, even more preferably 0.4 mass% or more and 2.0 mass% or less, and particularly preferably 0.5 mass% or more and 1.5 mass% or less, based on the total mass of the polishing composition. When the polishing composition contains two or more kinds of inorganic salts, the concentration (content) of the inorganic salt means the total amount of these.
[0064] [Dispersion medium] The polishing composition according to the present invention preferably further contains a dispersion medium. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferable as the dispersion medium. That is, according to a more preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above "substantially" means that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.
[0065] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.
[0066] [pH and pH adjusters] From the viewpoint of safety, the pH of the polishing composition according to the present invention is preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. In addition, from the viewpoint of improving the polishing rate of the surface of the object to be polished containing a material other than polysilicon (e.g., silicon oxide), the pH is preferably 7.0 or less, more preferably less than 5.0, even more preferably 4.5 or less, and particularly preferably 4.0 or less. That is, the pH of the polishing composition according to the present invention is preferably 1.0 or more and 7.0 or less, more preferably 1.0 or more and less than 5.0, and even more preferably 1.5 or more and 4.5 or less.
[0067] The polishing composition of the present invention may contain a pH adjuster for adjusting pH. The pH adjuster may be either an acid or a base, and may be either an inorganic compound or an organic compound. The pH adjuster may be used alone or in combination of two or more kinds.
[0068] Specific examples of acids that can be used as a pH adjuster include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid; and organic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, diglycolic acid, 2-furancarboxylic acid, 2,5-furandicarboxylic acid, 3-furancarboxylic acid, 2-tetrahydrofurancarboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid.
[0069] Bases that can be used as pH adjusters include amines such as aliphatic amines and aromatic amines, organic bases such as quaternary ammonium hydroxides, hydroxides of alkali metals such as sodium hydroxide and potassium hydroxide, hydroxides of Group 2 elements, and ammonia.
[0070] The amount of pH adjuster to be added is not particularly limited, and can be appropriately adjusted so that the polishing composition has a desired pH. The pH of the polishing composition can be measured, for example, by a pH meter, and specifically, can be measured by the method described in Examples.
[0071] [Electrical Conductivity of Polishing Composition] The electrical conductivity (EC) of the polishing composition according to the present invention is not particularly limited, but is preferably 1 mS / cm or more, more preferably 3 mS / cm or more. The electrical conductivity (EC) of the polishing composition according to the present invention is preferably 20 mS / cm or less, more preferably 15 mS / cm or less. That is, the electrical conductivity (EC) of the polishing composition according to the present invention is preferably 1 mS / cm or more and 20 mS / cm or less, more preferably 3 mS / cm or more and 15 mS / cm or less. If the electrical conductivity (EC) of the polishing composition is in such a range, the polishing rate of materials other than polysilicon (e.g., silicon oxide) can be improved. In addition, the repulsion between abrasive grains can be appropriately adjusted to ensure stability. The electrical conductivity of the polishing composition can be adjusted by the type and amount of inorganic salt, pH adjuster, etc. The electrical conductivity (EC) of the polishing composition can be measured by the method described in the Examples.
[0072] [Other ingredients] The polishing composition of the present invention may further contain other components, as necessary, such as a complexing agent, a metal corrosion inhibitor, a preservative, an antifungal agent, an oxidizing agent, a reducing agent, a surfactant, etc. Preferable components, the preservative and the antifungal agent, will be described below.
[0073] (Preservatives and fungicides) Examples of preservatives and antifungal agents that can be added to the polishing composition of the present invention include isothiazoline preservatives such as 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one, paraoxybenzoic acid esters, and phenoxyethanol, etc. These preservatives and antifungal agents may be used alone or in combination of two or more kinds.
[0074] [Form of polishing composition] The polishing composition according to the present invention is typically supplied to an object to be polished in the form of a polishing liquid containing the polishing composition, and is used to polish the object to be polished. The polishing composition according to the present invention may be used as a polishing liquid after dilution (typically diluted with water), or may be used as a polishing liquid as it is. That is, the concept of the polishing composition according to the present invention includes both a polishing composition (working slurry) that is supplied to an object to be polished and used to polish the object to be polished, and a concentrated liquid (original working slurry liquid) that is diluted and used for polishing. The concentration ratio of the concentrated liquid can be, for example, about 2 to 100 times on a volume basis, and is usually about 3 to 50 times.
[0075] [Polished object] The object to be polished according to the present invention is not particularly limited, and examples thereof include single crystal silicon, polycrystalline silicon (polysilicon), polycrystalline silicon doped with n-type or p-type impurities, amorphous silicon, amorphous silicon doped with n-type or p-type impurities, silicon oxide, silicon nitride, silicon carbonitride (SiCN), metals, SiGe, carbon-containing materials, and the like.
[0076] Examples of objects to be polished that contain silicon oxide include a TEOS-type silicon oxide film (hereinafter simply referred to as "TEOS" or "TEOS film") produced using tetraethyl orthosilicate as a precursor, a high density plasma (HDP) film, an undoped silicate glass (USG) film, a phosphorus silicate glass (PSG) film, a boron-phosphorus silicate glass (BPSG) film, and a rapid thermal oxidation (RTO) film.
[0077] Examples of metals include tungsten, copper, aluminum, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, and osmium.
[0078] Examples of carbon-containing materials include amorphous carbon, spin-on carbon (SOC), diamond-like carbon (DLC), nanocrystalline diamond, graphene, low-k materials such as SiOC (carbon-containing silicon oxide in which SiO2 is doped with C), silicon carbide, etc. Films containing carbon-containing materials can be formed by CVD, PVD, spin coating, etc.
[0079] The object to be polished may be a commercially available product or may be produced by a known method.
[0080] Among these, an object to be polished containing polysilicon is preferable. Therefore, according to a preferred embodiment of the present invention, the polishing composition is used for polishing an object to be polished containing polysilicon.
[0081] [Method of manufacturing the polishing composition] The method for producing the polishing composition according to the present embodiment is not particularly limited, and can be obtained, for example, by stirring and mixing abrasive grains, a polishing rate suppressor, a defect reducing agent, and other additives added as necessary. The details of each component are as described above.
[0082] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C. Heating may be performed to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.
[0083] [Polishing method and semiconductor substrate manufacturing method] As described above, the polishing composition according to the present invention is particularly suitable for use in polishing an object to be polished that contains polysilicon. Therefore, the present invention provides a polishing method for polishing an object to be polished that contains polysilicon with the polishing composition according to the present embodiment. The present invention also provides a method for producing a semiconductor substrate, comprising a step of polishing a semiconductor substrate that contains polysilicon by the above-mentioned polishing method.
[0084] As a polishing device, a general polishing device can be used that is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.
[0085] The polishing pad may be made of any material, including general nonwoven fabric, polyurethane, porous fluororesin, etc. It is preferable that the polishing pad has grooves formed thereon to allow the polishing liquid to accumulate.
[0086] Regarding the polishing conditions, for example, the rotation speed of the polishing table (platen) and carrier (head) was 10 rpm (0.17 s -1 ) or more 500rpm (8.33s -1 The pressure applied to the substrate having the object to be polished (polishing pressure) is preferably 0.5 psi (3.45 kPa) or more and 10 psi (68.9 kPa) or less.
[0087] The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump, etc. is adopted. There is no limit to the amount of the composition supplied, but it is preferable that the surface of the polishing pad is always covered with the polishing composition according to the present invention.
[0088] The polishing composition according to the present embodiment may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition according to the present invention may be prepared by diluting the stock solution of the polishing composition, for example, three times or more, with a diluent such as water.
[0089] [Polishing speed] As described above, the polishing composition of the present invention can suppress the polishing rate of polysilicon. Specifically, the polishing rate of polysilicon is preferably 35 Å / min or less, more preferably 32 Å / min or less, and even more preferably 30 Å / min or less.
[0090] [Number of defects] As described above, the polishing composition of the present invention can reduce the number of defects on the surface of polysilicon after polishing. Specifically, the number of defects of 0.08 μm or more is preferably 10,000 or less, more preferably 5,000 or less, and even more preferably 3,000 or less (lower limit: 0). The number of defects is a value measured by the method described in the examples.
[0091] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0092] The present invention encompasses the following aspects and configurations. 1. A polishing composition comprising an abrasive grain, a polishing rate suppressor that suppresses the polishing rate of polysilicon, and a defect reducing agent that reduces defects on the surface of polysilicon, wherein the polishing rate suppressor is a water-soluble polymer having a polyoxyalkylene chain and having a number average molecular weight of 200 or more and 600 or less, and a content of a component having a molecular weight of 700 or more exceeding 0% by mass and less than 1% by mass: 2. The polishing composition according to 1 above, wherein the water-soluble polymer having a polyoxyalkylene chain is polypropylene glycol. 3. The polishing composition according to 1. or 2. above, wherein the defect inhibitor is a water-soluble polymer having an alcoholic hydroxyl group in a side chain. 4. The polishing composition according to any one of 1. to 3. above, wherein the abrasive grains are anion-modified colloidal silica. 5. The polishing composition according to any one of 1. to 4. above, having a pH of 1.0 or more and less than 5.0: 6. The polishing composition according to any one of 1. to 5. above, further comprising an inorganic salt: 7. The polishing composition according to any one of 1. to 6. above, further comprising a dispersion medium: 8. The polishing composition according to any one of 1. to 8. above, which is used for polishing an object to be polished containing polysilicon: 9. A polishing method comprising polishing an object to be polished containing polysilicon with the polishing composition according to any one of 1. to 8. above: 10. A method for producing a semiconductor substrate, comprising the step of polishing a semiconductor substrate containing polysilicon by the polishing method described in 9 above. EXAMPLES
[0093] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (20°C to 25°C) / relative humidity 40% RH to 50% RH. Each physical property was measured as follows.
[0094] <Average secondary particle size of abrasive grains> The average secondary particle diameter of the abrasive grains was measured as the volume average particle diameter (arithmetic mean diameter based on volume; Mv) using a dynamic light scattering particle size / particle size distribution analyzer UPA-UTI151 (manufactured by Nikkiso Co., Ltd.).
[0095] <Zeta potential of abrasive grains> The zeta potential of the abrasive grains was measured using a zeta potential measuring device manufactured by Otsuka Electronics Co., Ltd. (product name "ELS-Z").
[0096] <pH of polishing composition> The pH of the polishing composition was measured using a glass electrode type hydrogen ion concentration indicator (Model: F-23, manufactured by Horiba, Ltd.) by performing three-point calibration using standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution, pH: 6.86 (25°C), carbonate pH buffer solution, pH: 10.01 (25°C)). The glass electrode was then placed in the polishing composition and the pH value was measured after stabilization for at least 2 minutes.
[0097] <Measurement of the number average molecular weight of the polishing rate suppressor (water-soluble polymer having a polyoxyalkylene chain) and the content of components with a molecular weight of 700 or more> A method for investigating the ratio of each polymer in a water-soluble polymer having a polyoxyalkylene chain (separation of polishing rate suppressors by high performance liquid chromatography) The samples of the water-soluble polymer having a polyoxyalkylene chain of the examples and comparative examples were separated into the peaks of each polymer using UltiMate 3000+CAD manufactured by Thermo Fisher Scientific. The column was manufactured by Tosoh Corporation, and water and acetonitrile were used as the eluent, and the gradient method was used under the conditions of an oven temperature of 30°C and a flow rate of 0.6 ml / min to separate into the peaks of each polymer. The abundance ratio of each polymer was determined by dividing the peak area of any polymer by the sum of the areas of all peaks obtained from the water-soluble polymer having a polyoxyalkylene chain. The number average molecular weight of the water-soluble polymer having a polyoxyalkylene chain was determined as the sum of the products of the molecular weight of the polymer and the abundance ratio of the polymer from the abundance ratio of each polymer in the water-soluble polymer having a polyoxyalkylene chain determined using high performance liquid chromatography (HPLC).
[0098] <Weight average molecular weight of polymer other than polishing rate suppressor> The weight average molecular weight of the polymer other than the polishing rate suppressor was determined by gel permeation chromatography (GPC) using the weight average molecular weight (converted into polyethylene glycol). The weight average molecular weight was measured using the following apparatus and conditions: GPC equipment: Shimadzu Corporation Model: Prominence + ELSD detector (ELSD-LTII) Column: VP-ODS (Shimadzu Corporation) Mobile phase A:MeOH B: 1% acetic acid solution Flow rate: 1mL / min Detector: ELSD temp. 40℃, Gain 8, N2GAS 350kPa Oven temperature: 40℃ Injection volume: 40μL.
[0099] <Electrical Conductivity of Polishing Composition> The electrical conductivity (EC) of the polishing composition was measured with a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71 LAQUA (registered trademark)).
[0100] <Sulfonic acid immobilized colloidal silica> The sulfonic acid-fixed colloidal silica contained in the polishing composition was prepared by using colloidal silica having an average secondary particle diameter of 68.9 nm, according to the method described in “Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups”, Chem. Commun. 246-247 (2003).
[0101] <Polypropylene glycol> The following six types of polypropylene glycol (PPG1 to PPG6) were prepared: Polypropylene glycol 1 (also referred to as PPG1): Polypropylene glycol having a number average molecular weight of 489.9 and a molecular weight of 700 or more of 1.06% by mass. Polypropylene glycol 2 (also referred to as PPG2): The above PPG1 was treated with activated carbon to prepare polypropylene glycol 2 having 0 mass % of components with a molecular weight of 700 or more and a number average molecular weight of 482.2.
[0102] The treatment of removing high molecular weight polypropylene glycol (water-soluble polymer having a polyoxyalkylene chain) with activated carbon was carried out using Kuraray Coal (registered trademark) GW-H, which is activated carbon manufactured by Kuraray Co., Ltd. More specifically, the activated carbon was washed with pure water, and then mixed with a 12% by mass aqueous solution of the polypropylene glycol (water-soluble polymer having a polyoxyalkylene chain) to be treated, and stirred for 2 hours to adsorb the high molecular weight components onto the activated carbon. The activated carbon was removed using a 0.2 um membrane filter of Ultipore (registered trademark) N66 manufactured by Pall Corporation, and separated into activated carbon and polypropylene glycol aqueous solution by suction filtration.
[0103] Polypropylene glycol 3 (also referred to as PPG3): Polypropylene glycol having a molecular weight of 700 or more (2.22% by mass) and a number average molecular weight of 491.8 Polypropylene glycol 4 (also referred to as PPG4): Polypropylene glycol having a molecular weight of 700 or more (2.97% by mass) and a number average molecular weight of 534.3 Polypropylene glycol 5 (also referred to as PPG5): Polypropylene glycol having a molecular weight of 700 or more (1.44% by mass) and a number average molecular weight of 518.3 Polypropylene glycol 6 (also referred to as PPG6): Polypropylene glycol having a number average molecular weight of 498.8 and containing 1.00% by mass of components with a molecular weight of 700 or more.
[0104] Example 1 <Preparation of Polishing Composition> The above PPG1 and PPG2 were mixed in a mass ratio of PPG1:PPG2=75:25 to prepare a polishing rate suppressor 1 (mixing temperature: 25° C., mixing time: 10 minutes). The number average molecular weight of the obtained polishing rate suppressor 1 was 496.4, and the content of components having a molecular weight of 700 or more was 0.82 mass%.
[0105] The sulfonic acid-fixed colloidal silica (average secondary particle diameter: 68.9 nm) prepared above was added to water as a dispersion medium so that the final concentration was 2.3 mass%. Furthermore, the polishing rate suppressor 1 was added to a final concentration of 0.6 mass%, butenediol-vinyl alcohol copolymer (polymerization degree: 300, manufactured by Mitsubishi Chemical Corporation, product name: Nichigo G-Polymer AZF8035W) as a defect reducing agent was added to a final concentration of 750 mass ppm, and ammonium sulfate (manufactured by Toyama Pharmaceutical Co., Ltd.) as an inorganic salt was added to a final concentration of 0.5 mass%, and the mixture was stirred and mixed (stirring temperature: 25°C, stirring time: 20 minutes). The pH of the polishing composition was adjusted to pH 2.1 using nitric acid, and the polishing composition 1 was completed. The zeta potential of the sulfonic acid-fixed colloidal silica in the polishing composition 1 was -55 mV, and the electrical conductivity (EC) of the polishing composition 1 was 12.0 mS / cm.
[0106] Example 2 The above PPG1 and PPG2 were mixed in a mass ratio of PPG1:PPG2=90:10 to prepare a polishing rate suppressor 2. The obtained polishing rate suppressor 2 had a number average molecular weight of 498.9 and a content of components having a molecular weight of 700 or more of 0.95 mass%.
[0107] Polishing composition 2 was prepared in the same manner as in Example 1, except that the polishing rate suppressor 1 was replaced with the polishing rate suppressor 2 obtained above.
[0108] Example 3 The above PPG1 and PPG2 were mixed in a mass ratio of PPG1:PPG2=85:15 to prepare polishing rate suppressor 3. The obtained polishing rate suppressor 3 had a number average molecular weight of 497.5 and a content of components having a molecular weight of 700 or more of 0.89 mass%.
[0109] Polishing composition 3 was prepared in the same manner as in Example 1, except that the polishing rate suppressor 1 was replaced with the polishing rate suppressor 3 obtained above.
[0110] Example 4 The above PPG1 and PPG2 were mixed in a mass ratio of PPG1:PPG2=45:55 to prepare polishing rate suppressor 4. The obtained polishing rate suppressor 4 had a number average molecular weight of 493.7 and a content of components having a molecular weight of 700 or more of 0.47 mass%.
[0111] Polishing composition 4 was prepared in the same manner as in Example 1, except that the polishing rate suppressor 1 was replaced with the polishing rate suppressor 4 obtained above.
[0112] Example 5 The above PPG1 and PPG2 were mixed in a mass ratio of PPG1:PPG2=30:70 to prepare polishing rate suppressor 5. The obtained polishing rate suppressor 5 had a number average molecular weight of 489.9 and a content of components having a molecular weight of 700 or more of 0.31 mass%.
[0113] Polishing composition 5 was prepared in the same manner as in Example 1, except that the polishing rate suppressor 1 was replaced with the polishing rate suppressor 5 obtained above.
[0114] Comparative Example 1 Comparative Polishing Composition 1 was prepared in the same manner as in Example 1, except that PPG2 was used as the polishing rate suppressor instead of the polishing rate suppressor 1.
[0115] Comparative Example 2 Comparative polishing composition 2 was prepared in the same manner as in Example 1, except that PPG3 was used as the polishing rate suppressor instead of the polishing rate suppressor 1.
[0116] Comparative Example 3 Comparative Polishing Composition 3 was prepared in the same manner as in Example 1, except that PPG4 was used as the polishing rate suppressor instead of the polishing rate suppressor 1.
[0117] Comparative Example 4 Comparative Polishing Composition 4 was prepared in the same manner as in Example 1, except that PPG5 was used as the polishing rate suppressor instead of the polishing rate suppressor 1.
[0118] Comparative Example 5 Comparative Polishing Composition 5 was prepared in the same manner as in Example 1, except that PPG1 was used as the polishing rate suppressor instead of the polishing rate suppressor 1.
[0119] Comparative Example 6 Comparative Polishing Composition 6 was prepared in the same manner as in Example 1, except that PPG6 was used as the polishing rate suppressor instead of the polishing rate suppressor 1.
[0120] [evaluation] A silicon wafer (300 mm, blanket wafer) having a polysilicon film with a thickness of 5000 Å formed on its surface was prepared as a polishing object. The polishing compositions obtained in the above Examples and Comparative Examples were used to polish the polishing object under the following conditions: <Polishing conditions> Polishing machine: 300mm polishing machine (manufactured by Ebara Corporation, model number: F-REX300E) Polishing pad: Polyurethane pad (Nitta DuPont, IC1000) Pressure: 2.0 psi (13.79 kPa) Polishing platen rotation speed: 31 rpm Carrier (head) rotation speed: 30 rpm Supply of polishing composition: free-flowing Flow rate of polishing composition: 200ml / min Polishing time: 60 seconds.
[0121] <Polishing speed> The polishing speed (polishing rate) of the object to be polished was calculated by the following formula.
[0122]
number
[0123] The film thickness of the object to be polished before and after polishing was measured using an optical interference type film thickness measuring device (KLA Tencor Corporation, model number: ASET-F5X), and the polishing rate was calculated by dividing the difference by the polishing time.
[0124] (Cleaning equipment and cleaning conditions) After the object was polished under the above polishing conditions, the polished object was removed from the polishing table (platen). Next, in the same polishing apparatus, the polished object was cleaned by a cleaning method in which the polished object was rubbed with a polyvinyl alcohol (PVA) sponge, which was a cleaning brush, under pressure and under the following conditions, using the following cleaning solution: Equipment: 300mm polishing machine (Ebara Corporation, model number: F-REX300E) Cleaning solution: 0.3% ammonia water Cleaning brush rotation speed: 100 rpm Rotation speed of object to be cleaned (polished object): 100 rpm Flow rate of cleaning solution: 1000mL / min Cleaning time: 20 seconds.
[0125] The number of defects (number of organic residues) of 0.08 μm or more on the surface of the polished object obtained by the above cleaning was evaluated according to the following method. In detail, defects of 0.08 μm or more on the entire surface of the polished object (excluding the outer periphery 5 mm) were detected using a defect detection device (wafer inspection device) "Surfscan SP5" manufactured by KLA-TENCOR Corporation. The number of organic residues was counted by observing all the detected defects with a review SEM (RS-6000, manufactured by Hitachi High-Technologies Corporation).
[0126] The configurations and evaluation results of the polishing compositions of the Examples and Comparative Examples are shown in the following Table 1. In addition, in the following Table 1, the inorganic salts and pH adjusters are omitted.
[0127] [Table 1]
[0128] As is clear from Table 1 above, when the polishing compositions of the Examples are used, it is possible to suppress the polishing rate of polysilicon while reducing defects (e.g., organic residues) on the polysilicon surface. In the case of the polishing composition of Comparative Example 1, which contains a polishing rate suppressor having a content of 0 mass% of a component having a molecular weight of 700 or more, it is found that the number of defects is reduced but the suppression of the polishing rate of polysilicon is insufficient. In the case of the polishing compositions of Comparative Examples 2 to 6, which contain a polishing rate suppressor having a content of 1 mass% or more of a component having a molecular weight of 700 or more, it is found that the polishing rate of polysilicon can be suppressed but the number of defects increases.
Claims
1. Abrasive grains and a polishing rate suppressor that suppresses the polishing rate of polysilicon; a defect reducing agent that reduces defects on a surface of the polysilicon; A polishing composition comprising: The polishing composition, wherein the polishing rate suppressor is a water-soluble polymer having a polyoxyalkylene chain, the number average molecular weight of which is 200 or more and 600 or less, and the content of components having a molecular weight of 700 or more is more than 0 mass% and less than 1 mass%.
2. The polishing composition according to claim 1 , wherein the water-soluble polymer having a polyoxyalkylene chain is polypropylene glycol.
3. The polishing composition according to claim 1 , wherein the defect inhibitor is a water-soluble polymer having an alcoholic hydroxyl group in a side chain.
4. The polishing composition according to claim 1 , wherein the abrasive grains are anion-modified colloidal silica.
5. The polishing composition according to claim 1 , having a pH of 1.0 or more and less than 5.
0.
6. The polishing composition of claim 1 , further comprising an inorganic salt.
7. The polishing composition according to claim 1 , further comprising a dispersion medium.
8. The polishing composition according to claim 1 , which is used for polishing an object containing polysilicon.
9. A polishing method comprising polishing an object containing polysilicon with the polishing composition according to any one of claims 1 to 8.
10. A method for manufacturing a semiconductor substrate, comprising the step of polishing a semiconductor substrate containing polysilicon by the polishing method according to claim 9.
Citation Information
Patent Citations
Polishing composition
JP2013021292A